Transcutaneous Carbon Dioxide Measurements in Women Receiving Intrathecal Morphine for Cesarean Delivery: A Prospective Observational Study. (March 2017) - Bauchat, Jeanette R.; McCarthy, Robert; Fitzgerald, Paul; Kolb, Stephen; Wong, Cynthia A.
Abstract : BACKGROUND: Neuraxial morphine is the most commonly used analgesic technique after cesarean delivery. The incidence of respiratory depression is reported to be very low (0%–1.2%) in this patient population as measured by pulse oximetry and respiratory rates. However, hypercapnia may be a more sensitive measure of respiratory depression. In the current study, the incidence of hypercapnia events (transcutaneous CO2 [TcCO2 ] >50 mm Hg) for ≥2-minute duration was evaluated using the Topological Oscillation Search with Kinematical Analysis monitor in women who received intrathecal morphine for postcesarean delivery analgesia. METHODS: Healthy women (>37 weeks of gestation) scheduled for a cesarean delivery with spinal anesthesia with intrathecal morphine were recruited. Baseline STOP-BANG sleep apnea questionnaire and TcCO2 readings were obtained. Spinal anesthesia was initiated with 12 mg hyperbaric bupivacaine, 15 µg fentanyl, and 150 µg morphine. The Topological Oscillation Search with Kinematical Analysis monitor was reapplied in the postanesthesia care unit and TcCO2 measurements obtained for up to 24 hours. Supplemental opioid administration and adverse respiratory events were recorded. The primary outcome was the incidence of hypercapnia events, defined as a TcCO2 reading >50 mm Hg for ≥2 minutes in the first 24 hours after delivery. RESULTS: Of the 120 women who were recruited, 108 completed the study. Thirty-five women (32%; 99.15% confidence interval, 21%–45%) reached the primary outcome of a sustained hypercapnia event. The median time (interquartile range [IQR]) from intrathecal morphine administration to the hypercapnia event was 300 (124–691) minutes. The median (IQR) number of events was 3 (1–6) and longest duration of an event was 25.6 (8.4–98.7) minutes. Baseline median (IQR) TcCO2 measurements were 35 (30–0) mm Hg and postoperatively, median (IQR) TcCO2 measurements were 40 (36–43) mm Hg, a difference of 5 mm Hg (99.15% confidence interval of the difference 2–8 mm Hg, P < .001). The incidence of hypercapnia events was 5.4% in women with a baseline TcCO2 value ⩽31 mm Hg, 22.5% with a baseline TcCO2 between 32 and 38 mm Hg, and 77.4% with a baseline TcCO2 >38 mm Hg ( P < .001). CONCLUSIONS: Hypercapnia events (>50 mm Hg for ≥2-minute duration) occurred frequently in women receiving 150 μg intrathecal morphine for postcesarean analgesia. Higher baseline TcCO2 readings were observed in women who had hypercapnia events. Abstract : Supplemental Digital Content is available in the text.